Fungsi Dan Makna Kain Adat Tolaki Di Kota Kendari - Iinfantri Wahid; Evang Asmawati (Jayapangus Press, 2018)
The formulation of the research problem is 1) What is the meaning contained in the form and motif and appearance of traditional cloth (weaving) in the Tolaki culture in Kendari City ?, and 2) What is the function and value of traditional cloth in Tolaki culture in Kendari City? The method used in this study is a descriptive qualitative method to provide an explanation of the function and meaning of Tolaki traditional cloth in Kendari City. Data obtained through direct interviews with research informants related to the function and meaning of Tolaki traditional cloth in Kendari City The results of the study found that the meaning contained in the culture and motifs and appearance of traditional cloth (weaving) in Tolaki culture in Kendari City were a) Wulele sanggula which meant defense sources, the good name of the country, the determination of leaders, prosperity of the people and justice / holiness. b) Pinelawa means the prosperity of the people, the main source of people's power in administering the government, c) Pinesewi or an alternative motive that means preserving the culture of the country's customs, d) Pineburu mbako which has continuous meaning, order and peace of the country and society, e) Pinetawawako which means protection. protect families and support the administration of government, and f) Penetobo which means courage. the husband's inspirers with oval trapezoidal motifs and sharp ends. While the function and value of traditional fabrics in Tolaki culture in Kendari City are as follows: a) As a dress used in dance dances at parties and life and traditional ceremonies. b) As a means of appreciation and giving to guests visiting the Tolaki area. c) As a means of valuing and giving in certain events and d) As a myth. tribal symbols are glorified because certain designs have their own meaning or meaning in the view of society.